Derivation of Optical Properties of Carbonaceous Aerosols by Monochromated Electron Energy-Loss Spectroscopy. (15th April 2014) - Zhu, Jiangtao; Crozier, Peter A.; Ercius, Peter; Anderson, James R.
Abstract Monochromated electron energy-loss spectroscopy (EELS) is employed to determine the optical properties of carbonaceous aerosols from the infrared to the ultraviolet region of the spectrum. It is essential to determine their optical properties to understand their accurate contribution to radiative forcing for climate change. The influence of surface and interface plasmon effects on the accuracy of dielectric data determined from EELS is discussed. Our measurements show that the standard thin film formulation of Kramers−Kronig analysis can be employed to make accurate determination of the dielectric function for carbonaceous particles down to about 40 nm in size. The complex refractive indices of graphitic and amorphous carbon spherules found in the atmosphere were determined over the wavelength range 200–1, 200 nm. The graphitic carbon was strongly absorbing black carbon, whereas the amorphous carbon shows a more weakly absorbing brown carbon profile. The EELS approach provides an important tool for exploring the variation in optical properties of atmospheric carbon.